2003
DOI: 10.1046/j.1365-2672.2003.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of the novel bacteriocin entomocin 9, and safety evaluation of its producer, Bacillus thuringiensis ssp. entomocidus HD9

Abstract: Aims: To identify and characterize new bacteriocins from a collection of 41 strains belonging to 27 subspecies of Bacillus thuringiensis, and to evaluate the safety of the producers. Methods and Results: Bacillus thuringiensis ssp. entomocidus HD9 produced in the culture supernatant an antimicrobial activity against Gram-positive bacteria including Listeria monocytogenes, one of four pathogenic Pseudomonas aeruginosa and several fungi. Production of the antibacterial activity, named entomocin 9, started during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 51 publications
4
80
0
3
Order By: Relevance
“…(Table 1). The inhibitory spectrum of this substance is rather similar to that of some BLS, such as lichenin (Pattnaik et al, 2001), entomocin 9 (Cherif et al, 2003) and BLS P40 .…”
mentioning
confidence: 51%
“…(Table 1). The inhibitory spectrum of this substance is rather similar to that of some BLS, such as lichenin (Pattnaik et al, 2001), entomocin 9 (Cherif et al, 2003) and BLS P40 .…”
mentioning
confidence: 51%
“…Complete amino acid sequencing using infusion tandem mass spectrometry indicated that each peptide is posttranslationally modified at its respective 21st, 25th, and 28th residues. Solution NMR studies on [ 13 C, 15 N] Trn-α and [ 13 C, 15 N]Trn-β were used to characterize these modifications. Analysis of multidimensional NOESY data shows that specific cysteines are linked to the α-carbons of the modified residues, forming three sulfur to α-carbon bridges.…”
mentioning
confidence: 99%
“…lactis that is used commercially in food preservation, has a broad spectrum of activity against other lactic acid bacteria (LAB) and most Gram-positive organisms (8). Although bacteriocins produced by LAB are the most widely investigated (9, 10), bacteriocins are also produced by most other Gram-positive (11)(12)(13)(14)(15) and Gram-negative (16,17) bacterial species.…”
mentioning
confidence: 99%
“…In this work, bacteriocins produced by three Bt strains (HD9, HD110 and HD125) were studied. Entomocin 9, an anionic bacteriocin produced by strain HD9 and entomocin 110, a bacteriocin produced by strain HD110 were previously described (Cherif et al, 2003;Cherif et al, 2008) but none of them has been purified to homogeneity and fully characterized at the biochemical level.…”
Section: Discussionmentioning
confidence: 99%
“…The main activity of each family is within the group of species producing it (Reeves, 1965). In the past few years, bacteriocin production was reported for many B. thuringiensis (Bt) strains: thuricin from strain HD2 (Favret and Yousten, 1989); tochicin from strain HD868 (Paik et al, 1997); thuricin 7 from strain BMG1.7 (Cherif et al, 2001); thuricin 439A and thuricin 439B from strain B439 (Ahern et al, 2003); entomocin 9 from strain HD9 (Cherif et al, 2003); bacthuricin F4 from strain BUPM4 (Kamoun et al, 2005), thuricin 17 from strain NEB17 (Gray et al, 2006); thuricin S from strain HD198 (Chehimi et al, 2007;Chehimi et al, 2010); entomocin 110 from strain HD110 (Cherif et al, 2008) and thuricin CD from strain DPC 6431 (Rea et al, 2010). Among these bacteriocins, three were reported to share the conserved N-terminal amino acid sequence DWTXWSXL (Kamoun et al, 2005;Gray et al, 2006;Chehimi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%